What Defines a Discipline and How We Teach and Study It? The Changing Scope and Role of the Subject Benchmark Statement for Politics and International Relations (IR) and Its Implications For the Teaching and Study of Politics and IR in Higher Education. - Blair, Alasdair; Craig, John; Gann, Rose; Honeyman, Victoria; Bellaby, Ross; Kolpinskaya, Ekaterina; Adams, Lucy; Parker, Jonathan (Political Studies, 2025)
The paper asks whether there is a typical Politics and IR curriculum before reviewing the content and design of the revised fifth edition of the Quality Assurance Agency (QAA) Politics and IR Subject Benchmark Statement that was launched in March 2023. The paper examines the manner by which the most recent edition differs from earlier subject benchmark statements and reflects on the implications of the strategic direction taken by the QAA to include new content areas that primarily focus on the development of disciplinary statements on Equality, diversity and inclusion (EDI), Accessibility and sustainability and Enterprise and entrepreneurship education (EED). The paper explores the implications of benchmark statements, given that while they are not a regulatory requirement, they nevertheless seek to define what can be expected of a graduate and are drawn upon by Higher Education Institutions (HEI) to inform the development and revision of Politics and IR undergraduate provision.